A 10-year follow-up study of psychosocial factors affecting couples after infertility treatment - Wischmann, Tewes; Scherg, Horst; Strowitzki, Thomas; Verres, Rolf (Human reproduction, 2012)
AbstractBACKGROUND. Little is known about the long-term course taken in life by couples who had undergone medically assisted reproduction (MAR). The aim of thi